The Effect of Healing Touch Therapy on Anxiety: Systematic Literature Review - Ramlah Ramlah; Yunie Armiyati; Mohammad Fatkhul Mubin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patient anxiety that is not handled properly can have an impact on the patient's deterioration in health status and quality of life. One of the therapies that can be applied is to overcome patients' anxiety disorders with touch healing therapy. . One therapy that can be applied to address anxiety disorders in patients with anxiety disorders is healing touch therapy. The purpose of this literature review was to determine the effect of healing touch therapy on anxiety. This literature review was conducted through a search of publications in Google Scholar, Somantic Scholar Proquest, and PubMed between 2019 and 2025 using the PRISMA method. The keywords used were